Waves of autocratization and democratization: a critical note on conceptualization and measurement. Issue 8 (16th November 2020) - Skaaning, Svend-Erik
ABSTRACT: Huntington famously distinguished between waves of democratization and de-democratization. Based on an alternative conceptualization of waves of regime change and novel data on episodes of democratization and autocratization, Lührmann and Lindberg identify three waves of autocratization where the most recent and ongoing began in 1994, affects a higher number of democracies, and unfolds relatively slowly and piecemeal. In this note, however, I argue that both their definition and their measurement of waves of democratization and autocratization are questionable. First, their operationalization of regime changes do not capture all degrees of change and it provides a skewed account since the criteria used to identify episodes of autocratization and democratization are not balanced. Second, their definition of waves of regime change deviates from the conventional understandings as it emphasizes relative trends in the number of upturns and downsturns rather than looking at the relative size or the relative number of autocratizations vis-à-vis democratizations. The last part of the article shows that an alternative, more intuitively appealing understanding and operationalization supports different conclusions regarding the periodization of waves.